2023
DOI: 10.1097/md.0000000000036322
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between vitamin-D deficiency and glycemia status and lipid profile in nondiabetics and prediabetics in Saudi population

Tarek Atia,
Mohammad H. Abdelzaher,
Somaia A. Nassar
et al.

Abstract: Vitamin D deficiency increases the risk of developing diabetes, dyslipidemia, and other chronic diseases. We aimed to investigate the relationship between vitamin D deficiency, glycemic levels, and lipid profiles in individuals with prediabetes and nondiabetes. This observational cross-sectional study was conducted on 249 adults who were divided into 2 groups based on the American Diabetes Association classification: nondiabetics and prediabetics. The serum vitamin D levels, lipid profiles, fasting blood gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…HDL-C was lower and TGs were higher in the hypovitaminosis D group [ 21 ]. Similar positive associations have been observed in numerous other studies conducted across various populations [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. A recent cross-sectional study confirmed that the percentage of individuals with dyslipidemia and dysglycemia was higher in subjects with low levels of vitamin D [ 33 ].…”
Section: Resultssupporting
confidence: 89%
“…HDL-C was lower and TGs were higher in the hypovitaminosis D group [ 21 ]. Similar positive associations have been observed in numerous other studies conducted across various populations [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. A recent cross-sectional study confirmed that the percentage of individuals with dyslipidemia and dysglycemia was higher in subjects with low levels of vitamin D [ 33 ].…”
Section: Resultssupporting
confidence: 89%
“…In Table 1, 3.3% of the patients were obese and 36.7% were overweight. Researchers at the Johns Hopkins Bloomberg School of Public Health discovered in a recent study that Americans with type 1 diabetes were or overweight at almost the same high rates as those without the disease [27,28].…”
Section: Discussionmentioning
confidence: 99%